Distribution and cellular localization of insulin-regulated aminopeptidase in the rat central nervous system - Fernando, Ruani N.; Larm, Jari; Albiston, Anthony L.; Chai, Siew Yeen (Journal of comparative neurology (1911), 2005)
Central infusions of angiotensin IV enhance spatial learning, memory retention and retrieval, neurotransmitter release, and long‐term potentiation via interaction with a specific, high‐affinity binding site. This site was recently purified and identified as the insulin‐regulated aminopeptidase (IRAP). This enzyme was previously characterized as the marker protein of specialized insulin‐responsive vesicles containing GLUT4 in muscle and adipose tissue. The present study provides the first comprehensive description of IRAP distribution in the adult rat brain. By using immunohistochemistry, IRAP was found to be highly expressed in selected olfactory regions, in septal and hypothalamic nuclei, throughout the hippocampal formation and cerebral cortex, and in motor and motor associated nuclei. IRAP was expressed exclusively in neurons in these regions. At the cellular level, IRAP was localized within cell bodies, excluding the nucleus, in a punctate vesicular pattern of expression. IRAP‐positive immunoreactivity was also found in some proximal processes but was not detected in synaptic nerve terminals. The neurochemical composition of IRAP‐containing neurons was further characterized by dual‐label immunohistochemistry. IRAP was expressed in cholinergic cell bodies of the medial septum, a source of cholinergic projections to the hippocampus and cerebral cortex. The distribution of IRAP in motor and motor‐associated nuclei; the colocalization of the enzyme with potential in vivo substrates, oxytocin and vasopressin in the hypothalamus; and the colocalization with GLUT4 in selected nuclei all suggest diverse physiological roles for IRAP in the rat central nervous system. J. Comp. Neurol. 487:372–390, 2005. © 2005 Wiley‐Liss, Inc.